Heat transfer generated in an underground mining environment (2018)
The article presents the results of the heat transfer analysis that is generated in an underground environment, specifically in coal mines. The objective is to observe the variability of the results, comparing mines with level access and inclined access; Another parameter of comparison has been the variation of the altitude at which the mines are located; The parameters of temperatures, air flow, relative humidity, air density, length of roads, quantity of explosive, number of miners, etc., have been collected in a coal mine located in the city of Cúcuta - Colombia. In order to speed up its use, it has used its own development software, which serves to model comfort and environmental quality underground.